Distribuição espacial de alguns atributos de um Argissolo Amarelo sob diferentes manejos no Perímetro irrigado do Baixo Acaraú - CE - Melo, Antonia Arleudina Barros de (2012)
Irrigated agriculture has intensified recent decades in arid and semiarid regions, increasing crop productivity and hence the need for the use of fertilizers and chemicals to meet the needs of plants and controlling pests and diseases. In order to analyze the impact of these practices on soil fertility, the study was conducted in an area with irrigated agriculture, irrigation district located in the Baixo Acaraú - CE, covering three different uses: forest regeneration (more than 10 years), cultivation of guava (four years) and banana cultivation (six years). We opened two trenches in the areas of forest and banana, for purposes of characterization and classification of the soil, and soil samples collected at depths of 0 -20 and 20 to 40cm in 100 georeferenced points and irregularly distributed in the area (50 in the area with banana, 30 in the area with guava and 20 in the natural vegetation). We analyzed the chemical attributes: pHH2O, pHKCl, Ca2+, Mg2+ Na+, K+, SB, H + Al, CEC and V%, P, N, sodium saturation, TOC, micronutrients (Fe, Cu, Mn, Zn), humic fractions (C-HUM, C-and C-FAF FAH) and granulometric fractions (sand, silt and clay). The variability, spatial dependence and time were analyzed using geostatistics and kriging techniques. The results show that most of the variables showed moderate spatial dependence for the 0-20cm depth and strong spatial dependence for the depth 20-40 cm, reflecting the practices and fertilization managements tend to become more random spatial variability of chemical properties in the area. Attributes Ca, Na and sodium saturation showed spatial and temporal variability of the levels with a gradual increase with time of cultivation. The sodium concentration tripled passing from 0.16 to 0.48 cmolc dm 3, while the sodium saturation was further increased going from 2.5 to 8.5 and from 2.5 to 12.5 of 0 -20 and 20 cm - 40 cm, respectively. The use of geostatistics and kriging interpolation of data enabled the identification of areas with different needs for phosphate and potash, to both cultures, showing that the use of average levels of P and K soil fertilization to practice increases the production costs, and generate environmental, or nutritional deficiencies by imbalance of soil nutrients. The cultivation of banana guava increased levels of soil nutrients in relation to the area with woods, but it is essential to adopt preventive measures to reduce impacts resulting from the continued use of agricultural fertilizers and pesticides coupled with the practice of irrigation.